Digital therapies in psychosocial rehabilitation and mental health - Marques, Antonio Jose, 1972-; Queiros, Ricardo, 1975- (Advances in psychology, mental health, and behavioral studies., 2022)
"This book introduces the reader to the latest digital innovations in the mental health field, points out new ways in patient care and describes the limits of its application with a goal to provide an understanding of the current state of digital mental health interventions and the factors influencing the ongoing transformation of the mental health sector"--